Constraints to Participation in Outdoor Recreational Activities among Malay Females in Pulau Indah, Selangor, Malaysia - Abdul Aziz, Nor Akmar (2006)
The study was carried out at four villages in Pulau Indah, Klang between December 2005 to March 2006. The data was collected by using a structured questionnaire. The purpose of this research is to identify the constraining factors affecting participation in outdoor recreational activities among Malay females. The objectives are to determine interpersonal, intrapersonal and structural constraining factors affecting Malay females level of participation in outdoor recreational activitiess at Pulau Indah, Klang, to identify the type of recreation activities Malay females are willing to participate in and to identify elements that would facilitate Malay females to participate in outdoor recreational activities based on their demographics profile and constraints. Interest in outdoor recreation and physical ability are the major factors in intrapersonal. Meanwhile for interpersonal constraints, the factors include friend’s participation, friend’s knowledge on the benefits of outdoor recreation and the respondent’s concern on accidents or injuries with the involvement of incompetent friends. Busy with commitment, do not have own transportation, do not have strong financial support and knowledge about the type of facilities provided which suit their preference are among the structural constraints for which the Malay females in Pulau Indah do not participate in outdoor recreation. The most serious constraint for Malay females in Pulau Indah is intrapersonal constraints. Respondents in Pulau Indah, Klang generally have the desire to participate in outdoor recreational activities, which are adventurous, challenging, and nature based such as rock climbing, trekking, jet skiing, sight-seeing and traveling. The different age group, occupation, marital status and education level provided the different types of outdoor recreation activity preferences. Malay females in Pulau Indah, reported that the key measure needed to encourage Malay females participation in outdoor recreational activities is through the dissemination of information concerning the benefits and importance of outdoor recreation. Activities offered should also be suitable with the Malay custom and culture, and that parks should provide good and comfortable facilities. Besides that, the parks also need to provide complete and proper equipments. Fitness, physical ability, the availability of time and safety also influence their participation in outdoor recreational activities. Respondents also suggested that Majlis Perbandaran Klang (MPK) provide quality recreational parks to attract their participation in outdoor recreational activities.